2022
DOI: 10.1021/acsami.2c08743
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transfer-Enabled Rapid Printing of Liquid Metal Circuits on Multiple Substrates

Abstract: Low-cost, rapid patterning of liquid metal on various substrates is a key processing step for liquid metal-based soft electronics. Current patterning methods rely on expensive equipment and specific substrates, which severely limit their widespread applications. Based on surface adhesion adjustment of liquid metal through thermal transferring toner patterns, we present a universal printing technique of liquid metal circuits. Without using any expensive processing steps or equipment, the circuit patterns can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…124 The formulations and the various processes used to obtain soft electronics by the 2D transfer approach are summarized in Table 3. Guo et al 125 (Figure 3A) reported on a liquid metal ink consisting of 18 wt % silver-coated copper microparticles embedded in NaOH-treated gallium-indium eutectic alloys (EGaIn). The incorporated silver-coated copper microparticles act as a rheology modifier, preventing the shaggy of printed EGaIn during print.…”
Section: D Transfer Approachmentioning
confidence: 99%
“…124 The formulations and the various processes used to obtain soft electronics by the 2D transfer approach are summarized in Table 3. Guo et al 125 (Figure 3A) reported on a liquid metal ink consisting of 18 wt % silver-coated copper microparticles embedded in NaOH-treated gallium-indium eutectic alloys (EGaIn). The incorporated silver-coated copper microparticles act as a rheology modifier, preventing the shaggy of printed EGaIn during print.…”
Section: D Transfer Approachmentioning
confidence: 99%
“…In addition, some studies have found that the specially treated toner has high adhesion to the LM, so the LM can be coated on the toner surface and then transferred to other flexible substrate surfaces (Zhao et al, 2020). In addition to the water transfer method, the toner pattern can also be transferred to a flexible substrate to make a template with selective adhesion to LM at a certain pressure and temperature (Guo et al, 2022). As shown in Figure 7E, first use a laser printer to print the toner pattern on the thermal transfer paper.…”
Section: Transfer Printing Substratementioning
confidence: 99%
“…Copyright@2020, RSC (E) Principle and the fabrication process of the liquid meal conductive traces. (Guo et al, 2022). Copyright@2022, ACS (F) LM patterns on smooth substrate and rough substrate (Guo et al, 2022).…”
Section: Lm-elastomer Compositesmentioning
confidence: 99%
See 2 more Smart Citations